2013
DOI: 10.3945/ajcn.112.046474
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific interactions between the IRS1 polymorphism and intakes of carbohydrates and fat on incident type 2 diabetes

Abstract: Our results indicate that IRS1 rs2943641 interacts with carbohydrate and fat intakes on incident T2D in a sex-specific fashion. A protective association between the rs2943641 T allele and T2D was restricted to women with low carbohydrate intake and to men with low fat intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 37 publications
(42 reference statements)
3
36
0
Order By: Relevance
“…Consistent with those observations, the results were replicated in the women of MESA African-American, non-Hispanic white, and Hispanic populations. The genetic effect of IRS1 variant rs2943641 on IR and T2D was susceptible to various dietary factors, as has been demonstrated in 3 other studies (7, 26, 27). One intervention study (7) found that rs2943641 interacted with dietary carbohydrate and fat on IR, and that rs2943641 CC carriers saw more benefit in terms of improved insulin sensitivity when choosing a high-carbohydrate and low-fat diet.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Consistent with those observations, the results were replicated in the women of MESA African-American, non-Hispanic white, and Hispanic populations. The genetic effect of IRS1 variant rs2943641 on IR and T2D was susceptible to various dietary factors, as has been demonstrated in 3 other studies (7, 26, 27). One intervention study (7) found that rs2943641 interacted with dietary carbohydrate and fat on IR, and that rs2943641 CC carriers saw more benefit in terms of improved insulin sensitivity when choosing a high-carbohydrate and low-fat diet.…”
Section: Discussionsupporting
confidence: 68%
“…In contrast, Zheng and colleagues (27) found that rs2943641 T allele carriers had lower risk of IR and metabolic syndrome when their dietary saturated fat-to-carbohydrate ratio was low. Another recent observational study (26) suggested a 3-way interaction between sex, rs2943641, and carbohydrate intake on incident T2D, and men and women showed opposite directions of the interaction between rs2943641 and carbohydrate intake. Our present study reports an interaction of rs2943641 with status of a micronutri-ent (vitamin D) on insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine articles [17][18][19][20][21][22][23][24][25] were excluded from the systematic review because of overlapping populations. Out of these 22 articles, a total of 13 cohort studies [26][27][28][29][30][31][32][33][34][35][36][37][38] were appraised in the systematic review and metaanalysis. The 13 selected articles included in the systematic review were moderately heterogeneous in terms of population demographics, carbohydrate intake parameters, and the assessment of confounding factors.…”
Section: Search Resultsmentioning
confidence: 99%
“…Although the majority of the enrolled subjects were middle-aged and free of chronic disease at baseline, healthcare professionals were predominant in the US cohorts and might not have been truly representative of the average population in the community. In two cohorts consisting exclusively of men 33,34 and another cohort, 36 the risks of diabetes were significantly elevated among the subjects with low-carbohydrate diets (relative risk range, 1.15-1.31). In contrast, the risks in women 30,31,38 were significantly lower (relative risk range, 0.63-0.79).…”
Section: Qualitative Summarymentioning
confidence: 99%